Exploring the Effects of Physical Activity Levels and Sleep Quality on Cognitive Failure in Elderly: A Cross-Sectional Study - Hatami, Farzaneh; Abolghasemi Atani, Shafagh; Caron, Valerie; Yousefi, Saheb (International Journal of Sport Studies for Health, 2025)
Abstract Objectives: Aging is a natural stage of life characterized by physiological and cognitive changes that increase the risk of cognitive failure. Among modifiable lifestyle factors, physical activity and sleep quality play a crucial role in maintaining cognitive function in older adults. Therefore, the present study aimed to examine the effects of physical activity levels and sleep quality on cognitive failure in Iranian older adults. Methods & Materials: To achieve the objectives of the study, a descriptive, cross-sectional study was conducted using a multistage cluster random sampling method. The study population consisted of adults aged 60 and older from five geographical regions of Iran. The data were collected using the Cognitive Failures Questionnaire (CFQ), Pittsburgh Sleep Quality Index (PSQI), and the CHAMPS Physical Activity Questionnaire for Older Adults. Finally, the data were analyzed using a two-way multivariate analysis of variance (MANOVA). Results: The results of the two-way multivariate analysis of variance (MANOVA) revealed significant main effects for both physical activity level and sleep quality, as well as a significant interaction effect between physical activity level and sleep quality on the subscales of cognitive failure (p<.001). Follow-up tests of the interaction using a simple main effects test indicated that the effect of physical activity level on all subscales of cognitive failure depended on sleep quality. Specifically, in older adults with good sleep quality, the effect of physical activity on cognitive variables was significantly larger and more robust (partial eta squared ranging from .142 to .382). This suggests that under conditions of optimal sleep quality, individuals experience more pronounced benefits from physical activity. Conversely, while the effect of physical activity was also statistically significant in older adults with poor sleep quality (partial eta squared ranging from .060 to .111), the magnitude of this effect was diminished. This implies that even with suboptimal sleep, physical activity remains beneficial, although its impact is less pronounced than when sleep quality is also optimal. Conclusion: The results revealed that the synergistic effect of physical activity and high-quality sleep is crucial for enhancing cognitive performance in the elderly. The beneficial effects of physical activity on cognitive performance were most pronounced when accompanied by optimal sleep quality. Consequently, it is recommended for health specialists and policymakers to prioritize integrated interventions that concurrently promote regular physical activity and offer strategies to improve sleep hygiene. Focusing on a single factor is unlikely to yield optimal results.